Hranice světů: staroseverský Midgard a Útgard ve strukturalistických a poststrukturalistických interpretacích = Borders of the worlds : old Norse Miðgarðr and Útgarðr in Structuralist and Post-Structuralist interpretations - Starý, Jiří (Religio, 2010)
The article tries to trace the structuralist and post-structuralist interpretations of the opposition of Miðgarðr and Útgarðr and their consequences for the understanding of some Old Norse rituals. After a brief overview of the sources and recent linguistic opinions about the origin of the words Ásgarðr, Miðgarðr and Útgarðr, the authors demonstrate the main features of the structuralist view of this basic mythical opposition, as it is present in the works of Einar Haugen and Eleazar Meletinsky. The paper then describes the implementation of this mythical opposition in the space organization of human settlement that was suggested by Kirsten Hastrup, and tries to support it by adding new material concerning the relation of fence (garðr) and the concept of helgi in Old Norse sources. -- The second part of the article is devoted to the presentation of post-structuralist attacks on the structuralist interpretation that - far from forming a united and consequent school - nevertheless hit some weak points in the structuralist view of the problem. Works by Margaret Clunies Ross, Gro Steinsland, Agneta Ney, and Frederik Stjernfelt criticize the oversimplifications of the structuralist interpretation, its understanding of Miðgarðr as closed universe, the absolute separation between Miðgarðr and Útgarðr, and the lack of understanding of the dynamics of the Old Norse mythical worldview. Especially in respect to the last mentioned problem the authors plead for a new interpretation of the landtaking process (landnám), that can be understood well in the Stjernfelt's concept of "polarization" as a process of dividing the natural and undifferentiated landscape into districts with different measure of sanctity. -- In conclusion the authors try to reconcile the structuralist and post-structuralist interpretations of Miðgarðr and Útgarðr as synchronic and diachronic views of the same phenomenon that pervaded the myth as well as the daily life of Old Norsemen.